Analysis of relationships among coastal alluvial fans and their contributing catchments in North Evoikos Gulf (Central Greece). - Valkanou, K.; Karymbalis, E.; Papanastassiou, D.; Gaki-Papanastassiou, K.; Giles, P. (Bulletin of the Geological Society of Greece, 2013)
This paper deals with the morphometric analysis of 42, late Holocene, coastal alluvial fans located along the coasts of the tectonically active North Evoikos Gulf in central Greece. Thirty six of the fans have been formed by streams that discharge along the east coast of the Gulf (Evia Island) while the rest are located on the opposite side (Continental Greece). Selected morphometric parameters of the drainage basins were measured using topographic maps at the scale of 1:50,000 while those of the fans were derived from detailed topographic diagrams at the scale of 1:5,000 utilizing ESRI’s ArcGIS9.3 software. Fans were classified into four groups according to the primary depositional processes (fluvial and/or debris flow). Another classification criterion was the relationship between the location of the fan-catchment system and the local tectonic patterns (active faults). Fan-basin morphometric relationships for each fan group were also investigated. A strong positive relation was found between the size of the fan and the drainage basin area while the correlation between drainage area and fan slope was negative. Large catchments located near fault terminations have formed gently sloping fans dominated by fluvial processes, whereas torrents with small rough drainage basins, developed on the footwall, have formed steep fans likely dominated by debris-flow along the east coast of the Gulf